How Institutions Shape Land Deals: The Role of Corruption - Matthias Bujko; Christian Fischer; Tim Krieger; Daniel Meierrieks (Center for Economic Studies and ifo Institute (CESifo), 2015)
Large-scale land acquisitions often take place in developing countries which are also known for their corruption-friendliness caused by weak institutional frameworks. We hypothesize that corruption indeed leads to more land deals. We argue that corrupt elites exploit poor institutional setups (characterized by corruption) to strike deals with domestic and international investors at the expense of the local population. Using panel data for 156 countries from 2000-2011, we provide evidence that large-scale land deals indeed occur more often in countries with higher levels of corruption. The estimated effects are also economically substantive and particularly relevant to economies with unsound institutions.
Keywords: F21; O13; Q15; 330; large-scale land acquisitions; land grabbing; foreign investments; weak institutions; corruption